Revisiting the Debt Sustainability Framework for Low-Income Countries. (Policy Papers; Policy Paper ;, 2012)
Introduced in 2005, the joint IMF-World Bank Debt Sustainability Framework (DSF) is a standardized framework for conducting public and external debt sustainability analysis (DSA) in low-income countries (LICs). It aims to help guide the borrowing decisions of LICs, provide guidance for creditors' lending and grant allocation decisions, and improve World Bank and IMF assessments and policy advice. The framework was previously reviewed in 2006 and 2009. This paper provides a comprehensive review of the framework to assess whether it remains adequate in light of changing circumstances in LICs. It reviews the DSF's performance to date, presents the results of recent analytical work by IMF and World Banks staffs, and discusses a number of areas in which the framework could be improved.